The Influence of US Political Interests on the Libyan Civil War - ABADI, Nardjes; NEIMI, Nadjla (جامعة الوادي - University of Eloued, 2023)
It can be argued that, Libyan civil war has witnessed an involvement by the Unites States of America by using its foreign policy there. This study aims to discuss the issue of American policy in the Libyan civil war. The study examines economic, military and political aspect of the Libyan uprising, plus to the United States interventions in each side. This work gives information and investigations about the Arab spring and the effect of America on it, besides to Muammar Qaddafi's regime before 2011 as considered the main reasons of the 2011 protests. This work presents the events and facts of Libyan uprising, and how it started from the demonstrations till it turned to a civil war, and how the international community act toward it. Also, the governmental division from 2011 until nowadays and how the terroristic organization and the Islamic States in Iraq and Syria impacted that effect the Libya war. This work adopted tools of the descriptive analytical method and the historical method to describe, analyse and narrate data from the uprising till the current situations. The study reveals the main results of the Libyan war and the effects of the American foreign policy in the state. ويمكن القول إن الحرب الأهلية الليبية شهدت تورطاً للولايات المتحدة الأمريكية باستخدام سياستها الخارجية هناك. تهدف هذه الدراسة إلى مناقشة موضوع السياسة الأمريكية في الحرب الأهلية الليبية. تتناول الدراسة الجوانب الاقتصادية والعسكرية والسياسية للانتفاضة الليبية، بالإضافة إلى تدخلات الولايات المتحدة في كل جانب. يقدم هذا العمل معلومات وتحقيقات حول الربيع العربي وتأثير أمريكا عليه، بالإضافة إلى نظام معمر القذافي قبل عام 2011 باعتباره الأسباب الرئيسية لاحتجاجات 2011. يعرض هذا العمل أحداث وحقائق الانتفاضة الليبية، وكيف بدأت منذ المظاهرات حتى تحولت إلى حرب أهلية، وكيف يتصرف المجتمع الدولي تجاهها. وأيضا الانقسام الحكومي منذ عام 2011 حتى يومنا هذا وكيف أثر التنظيم الإرهابي والدول الإسلامية في العراق وسوريا على ذلك في حرب ليبيا. اعتمد هذا العمل على أدوات المنهج الوصفي التحليلي والمنهج التاريخي في وصف وتحليل وسرد البيانات منذ الانتفاضة وحتى الأوضاع الراهنة. وتكشف الدراسة عن أبرز نتائج الحرب الليبية وتأثيرات السياسة الخارجية الأمريكية في الدولة.
Degree in Literature and Civilization
Keywords: Foreign Policy, Intervention, Arab spring, Libyan civil war; السياسة الخارجية، التدخل، الربيع العربي، الحرب الأهلية الليبية، أمريكا